2010
DOI: 10.1177/0300985810378648
|View full text |Cite
|
Sign up to set email alerts
|

Henipavirus: A Review of Laboratory Animal Pathology

Abstract: The genus Henipavirus contains two members-Hendra virus (HeV) and Nipah virus (NiV)-and each can cause fatal disease in humans and animals. HeV and Niv are currently classified as biosafety level 4, and NiV is classified as a category C priority pathogen. The aim of this article is to discuss the pathology of laboratory animal models of henipavirus infection and to assess their suitability as animal models for the development and testing of human therapeutics and vaccines. There has been considerable progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 82 publications
(237 reference statements)
1
37
0
Order By: Relevance
“…NiV and HeV both cause severe and often fatal respiratory disease and/or encephalitis in animals and humans. HeV was first isolated during an outbreak of respiratory and neurologic disease in horses and humans in Australia in 1994 (2)(3)(4)(5). To date, a total of 5 outbreaks of HeV involving human cases have been reported in Australia, and 7 human cases with a case fatality rate of 57% have been identified (6).…”
mentioning
confidence: 99%
“…NiV and HeV both cause severe and often fatal respiratory disease and/or encephalitis in animals and humans. HeV was first isolated during an outbreak of respiratory and neurologic disease in horses and humans in Australia in 1994 (2)(3)(4)(5). To date, a total of 5 outbreaks of HeV involving human cases have been reported in Australia, and 7 human cases with a case fatality rate of 57% have been identified (6).…”
mentioning
confidence: 99%
“…1,2,4,9,17,18 Other animals (such as mice, chickens, rats, rabbits and dogs) do not appear to develop clinical disease after experimental inoculation, but rabbits, dogs and rats develop a neutralising antibody response. 1,9,17,18 The necropsy findings in this case indicate that canine infection can be more extensive than indicated by previous experimental studies, suggesting that more research on canine HeV is required to understand this risk.…”
Section: Discussionmentioning
confidence: 99%
“…1,17,18 HeV can be isolated in the lung, spleen, kidney, brain, rectum, trachea, bladder, heart muscle, liver, lymph nodes, pleural fluid, urine and blood of infected cats. 17,18 Transmission study data also showed cat-to-cat transmission from sharing a cage, and cat-to-horse transmission, but not horseto-cat transmission. 1,4,9,19 Experimental data from pigs have raised the possibility of other animals serving as additional spillover hosts from flying foxes.…”
Section: Discussionmentioning
confidence: 99%
“…While the zoonotic potential of HeV has been evident since the initial outbreak and subsequent laboratory based studies (Williamson and Torres-Velez, 2010), the detection in 2011 and 2012 of natural HeV infection in dogs has been a significant development in the epidemiology of this virus. As there is evidence that these infections can be asymptomatic, laboratory testings for agent and antibody will be key investigative approaches.…”
Section: Discussionmentioning
confidence: 99%